2022
DOI: 10.2147/ijwh.s369151
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Testing of a New Short-Form of the Premenstrual Symptoms Questionnaire (PSQ-S)

Abstract: Purpose The Premenstrual Symptoms Questionnaire (PSQ) is a patient-reported outcome measurement tool for premenstrual symptoms. Although the PSQ is a very useful tool with 14 items to screen for a wide variety of premenstrual symptoms, not everyone will respond to all the questions. Fewer questions would be less burdensome on the respondents. We aimed to develop and analyze the psychometric properties of a short-form of the PSQ (PSQ-S). Patients and Methods The study pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(52 reference statements)
0
2
1
Order By: Relevance
“…There are several study limitations that should be examined and discussed. First, in this study, only 10% of women had PMS and 3% had PMDD, which was slightly less than the 20-30% observed in community samples 28 and the 5.9% of 303 healthy women aged 20-45 years assessed using the DSM-IV 15,29,30 , which suggests that our study participants might have been healthier than these other populations.…”
Section: Study Limitationscontrasting
confidence: 59%
“…There are several study limitations that should be examined and discussed. First, in this study, only 10% of women had PMS and 3% had PMDD, which was slightly less than the 20-30% observed in community samples 28 and the 5.9% of 303 healthy women aged 20-45 years assessed using the DSM-IV 15,29,30 , which suggests that our study participants might have been healthier than these other populations.…”
Section: Study Limitationscontrasting
confidence: 59%
“…More recently, the short-form of the PSQ (PSQ-S), consisting of nine items from the PSQ was developed and analyzed by CTT and IRT. 32 In CTT, the PSQ-S showed the same ability as the PSQ in the aspect of reliability, structural validity, and concurrent validity. Moreover, IRT showed that the all nine items in the PSQ-S performed well.…”
Section: Screening and Diagnostic Questionnairesmentioning
confidence: 92%
“…Furthermore, the PSQ has been adequately validated for reliability, and psychometric properties have been shown to be sound. More recently, the short‐form of the PSQ (PSQ‐S), consisting of nine items from the PSQ was developed and analyzed by CTT and IRT 32 . In CTT, the PSQ‐S showed the same ability as the PSQ in the aspect of reliability, structural validity, and concurrent validity.…”
Section: Introductionmentioning
confidence: 99%